2021
DOI: 10.3390/su132011241
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Management Policies, Practices, and Challenges in Ethiopia: A Systematic Review

Abstract: Municipal Solid Waste Management (MSWM) affects several spheres, including environmental, social, and economic activities. In Ethiopia, massive waste generation and unbalanced management have worsened the issue. Hence, this systematic review investigates the Ethiopian MSWM policy and legal frameworks, practices, and challenges. The Scopus and Web of Science databases and Google Scholar were used to search published and unpublished studies from 2005 to 2021, and a website search was used to find studies from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The predominant amount of waste in Ethiopia is dumped on open dumping sites [8], thereby causing environmental pollution and releasing greenhouse gases (GHG) like methane (CH 4 ) [45,80]. This is of particular importance, as MSW has been considered the third-largest source of anthropogenic CH 4 gas in the environment, accounting for 3-4% of global anthropogenic GHG emissions.…”
Section: Potentials and Challenges For Producing Compost Out Of Organ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The predominant amount of waste in Ethiopia is dumped on open dumping sites [8], thereby causing environmental pollution and releasing greenhouse gases (GHG) like methane (CH 4 ) [45,80]. This is of particular importance, as MSW has been considered the third-largest source of anthropogenic CH 4 gas in the environment, accounting for 3-4% of global anthropogenic GHG emissions.…”
Section: Potentials and Challenges For Producing Compost Out Of Organ...mentioning
confidence: 99%
“…When only considering CH 4 , total waste sectors are responsible for approximately 18% of global CH 4 emissions [4]. The average amount of CH 4 released from dumping sites in low-income countries in general and in Ethiopia in particular can be considered larger than the world average CH 4 release from open dumping sites, due to their large proportion of organic waste [45,87,88]. Consequently, a modeling study by Couth et al [89] found that 8.1% of all GHG emissions from Africa originated from landfills, which was considerably more than the global average of 3%.…”
Section: Potentials and Challenges For Producing Compost Out Of Organ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, 2.3 billion tons of solid waste are generated in cities annually and this is expected to reach 3.4 billion tons in 2050 [5]. Approximately 62 million tons of solid waste are produced in Sub-Saharan Africa each year; however, waste collection rates in developing countries are less than 70% [6]. The rate of household solid waste in low-income countries is increasing with an increment in population growth and the changes in the lifestyles of people.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in least-developed countries such as Ethiopia, an estimated 30 to 50% of solid waste produced in the urban area is left uncollected [ 7 ]. In Ethiopia, the average municipal solid waste generation rate ranges from 0.25 to 0.49 kg/capita/day [ 8 ]; moreover, it is not properly managed. This is due to the increase in the national population, the rising demand for food, urbanization, economic growth, and the improved lifestyle of people, which results in the increased generation of solid wastes in urban as well as rural areas of the country [ 9 ].…”
Section: Introductionmentioning
confidence: 99%